Adaptive multi user diversity meta scheduler to reduce energy consumption - Cédric Gueguen; Christopher Merlhe; Guillaume Terrier (Discover Applied Sciences)
Abstract Reducing energy consumption for economic purposes while fighting against global warming is a major concern in many fields of research. Particularly, in wireless networks a crucial issue remains the design of energy efficient radio resource allocation strategies without spoiling the Quality of Service (QoS) or the system capacity. This study focuses on reducing User Equipment (UE) energy consumption to achieve goals aforementioned as well as to increase their battery lifetime. In order to address this challenge, we propose a meta-scheduler acting before the scheduling process. The proposed solution entitled, Adaptative Multi User Diversity meta Scheduler (AMUDS), is able to manage the multi-user diversity usage made by schedulers depending on the traffic load of the cell and the spectral efficiency. This allows the adequate number of UEs in active mode during a time slot in order to minimize the transmission time and thus, to reduce their energy consumption. Performance evaluation emphasizes that this solution is compatible with the most acknowledged scheduling solutions while keeping their intrinsic properties.